Mecanismos de toxicidade de Duguetia furfuraceae A. St.-Hill no modelo de Drosophila melanogaster e avaliação do potencial antifúngico. - Pinho, Francisca Valéria Soares de Araújo (2015)
Duguetia furfuracea is a common shrub from Brazilian cerrado areas, known as "ata brava", often used as a medicinal plant especially in treatment of renal colic and rheumatism. However, pharmacological studies with extracts obtained from different parts of this plant have shown cytotoxic activity, bactericidal and anti-tumor. Thus, this study aimed to identify and quantify the phenolic compounds of the hydroalcoholic extract of leaves D. furfuracea (HEDP), methanol (Mt-OH) and ethyl acetate (Ac-OEt) fractions by HPLC, and carry out phytochemical screening for different classes of compounds. In addition the antioxidant activity by the DPPH and FRAP assays, toxicity of the crude extract in the Drosophila melanogaster model, and the antifungal/modulatory activity were evaluated. The phytochemical screening revealed the presence of alkaloids, tannins, xanthones, chalcones, flavonoids, aurones and phenolic acids. HPLC analysis revealed that major components of HEDF were caffeic acid (33.17 ± 0.03 mg/g) and rutin (20.56 ± 0.01 mg/g), for the Mt-OH fraction were, caffeic acid (32.47 ± 0.03 mg/g) and quercitrin (31.96 ± 0.03 mg/g), and for Ac-OEt fraction were, quercitrin (32.97 ± 0.03 mg/g) and isoquercitrin (31.56 ± 0.01 mg/g). Although highest levels of phenols and total flavonoids were found in Ac-OEt fraction, the crude extract showed the highest antioxidant (in vitro) potential. The toxicity of the extract was confirmed (in vivo) associating the extract with standard diet of D. melanogaster at different concentrations. The extract caused a significant increase in mortality on the third day of exposure of flies at higher concentrations (100 and 200 mg/ml). The 50mg/ml concentration promoted decrease in motility of flies. Interestingly, the activity of acetylcholinesterase (AchE) was increased in flies exposed to concentrations of 1 and 10mg/ml and inhibited by the concentration of 50 mg/ml of HEDF. The cell viability was significantly compromised flies at all HEDF concentrations (1, 10 and 50 mg/ml) although it has been observed a significant increase in production of reactive oxygen species flies exposed only in the concentration of 50mg/ml. In this context it was evaluated the influence of extract (ex vivo) in the activity of antioxidant defenses of D. melanogaster exposed to concentrations of 1 and 10 mg/ml of HEDF resulted in a significant increase in the activity of enzymes Glutathione s-transferase (GST), Superoxide dismutase (SOD) and catalase (CAT), however, for the concentration of 50 mg/ml of extract, there was a dramatic decrease in the activity of GST with no change in SOD activity and CAT. The cleavage of PARP investigated as a general index of cell death by apoptosis was confirmed in flies exposed to all HEDF concentrations. Yet exposure of the flies to HEDF 10 mg/mL significantly increased the phosphorylation of kinase ERK. The extract and fractions tested against Candida albicans, Candida tropicalis and Candida krusei showed no fungicidal activity since the minimum inhibitory concentration (MIC) was ≥ 1.024 μg/ml for all fungal strains tested. However, the HEDF and the fractions Ac-OEt and Mt-OH had a synergistic effect when combined with fluconazole, indicating modulatory action against fungi when associated with clinically relevant medicine. The HEDF and the fraction Mt-OH potentiated the effect of fluconazole when tested against C. kruzei, and the fraction Mt-OH also showed synergy with fluconazol against C. tropicalis. The fraction Ac-OEt potentiated the effect of fluconazol against C. albicans. The set of results suggests that oxidative stress may be an important mechanism underlying the toxicity induced by extract of D. furfuracea in Drosophila melanogaster. Additionally modulatory activity of the extract and fractions towards fluconazol improve the biomedical applications D. furfuracea.